STABILITY, INNOVATIONS AND COMPETITIVENESS OF ENTREPRENEURSHIP ORGANIZATIONS AS NATIONAL ECONOMY STRATEGIC RESOURCE AND INTERNAL MODERNISATION SOURCE - A. A. Lavrenova; M. N. Dudin (Модернизация, инновация, развитие, 2016)
Russian economy modernization problems are to be solved on the basis of innovations and very soon, since it is vital for the increase of competitiveness of national economy and economy of domestic enterprises. Discussed in the article are issues related to modern development of business as well as most actual directions of development connected with innovations and integration processes. Reasons of unpreparedness of Russian entrepreneurship for innovative development are revealed. Governmental measures and directions of innovative development are critically analyzed, examples from foreign experience are provided for. Directions of development and increase of competitiveness of enterprises on the basis of innovations and integration are proposed.